2022
DOI: 10.1016/j.survophthal.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence applications and cataract management: A systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…It has no connecting elements. As it can be expected, the homogeneous surface makes the lens more resistant to mechanical damage [33][34][35].…”
Section: Discussionmentioning
confidence: 79%
“…It has no connecting elements. As it can be expected, the homogeneous surface makes the lens more resistant to mechanical damage [33][34][35].…”
Section: Discussionmentioning
confidence: 79%
“…Using the scleral spur (SS) as a landmark, it was then possible to quantify the ACA width using parameters previously introduced for the UBM including the angle opening distance (AOD) at 500 μm from the scleral spur, the angle recess area (ARA) and the trabeculo-iris space [ 15 ]. With OCT technology, precise measurements made it possible to measure dynamic changes in the ACA occurring with dark-light variations [ 16 ], quantify ACA morphology modifications after laser peripheral iridotomy [ 17 , 18 ] or phacoemusification [ 19 , 20 ]. While OCT offers non-contact and is less dependent on observer’s training than slit-lamp gonioscopy, it also presents several drawbacks.…”
Section: Methodsmentioning
confidence: 99%
“…DR, age related macular degeneration (ARMD), retinopathy of prematurity (ROP), glaucoma and cataracts have all been identified as promising disease areas for AI [ 106 ]. A systematic review of AI in the management of people with cataracts found that AI-driven diagnosis was at least comparable, and at times superior to expert clinical diagnosis [ 107 ]. AI has demonstrated utility beyond diagnostic purposes with improved intraoperative lens selection and a subsequently reduced refractive error [ 108 ].…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%